2016
DOI: 10.14218/jcth.2016.00049
|View full text |Cite
|
Sign up to set email alerts
|

Limited Knowledge of Acetaminophen in Patients with Liver Disease

Abstract: Background and Aims: Unintentional acetaminophen overdose remains the leading cause of acute liver failure in the United States. Patients with underlying liver disease are at higher risk of poor outcomes from acetaminophen overdose. Limited knowledge of acetaminophen may be a preventable contributor to elevated rates of overdose and thus acute liver failure. The purpose of this study is to assess knowledge of acetaminophen dosing and presence of acetaminophen in common combination products in patients with liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Patients widely reported poor knowledge and understanding about the disease and its risk factors, associated complications and treatment. This lack of awareness has also been reported previously in an American study which suggested that patients with liver disease have limited knowledge about the safety of acetaminophen for pain management that can put them at risk of undermedication or overdose [64]. Another American study that involved liver transplant patients suggested that patients with a better understanding of their treatment and medication regimen were more likely to adhere to their treatment and can avoid the risk of hospitalisation [65].…”
Section: Discussionmentioning
confidence: 54%
“…Patients widely reported poor knowledge and understanding about the disease and its risk factors, associated complications and treatment. This lack of awareness has also been reported previously in an American study which suggested that patients with liver disease have limited knowledge about the safety of acetaminophen for pain management that can put them at risk of undermedication or overdose [64]. Another American study that involved liver transplant patients suggested that patients with a better understanding of their treatment and medication regimen were more likely to adhere to their treatment and can avoid the risk of hospitalisation [65].…”
Section: Discussionmentioning
confidence: 54%
“…Although the internet may serve as a source of health information for patients, the complexity of the primary literature, and potential misinformation may result in confusion rather than clarity. A survey of 401 patients with chronic liver disease showed that only 15.7% of patients were aware of the safe dose of acetaminophen, and less than 20% reported awareness that medications such as Norco, Vicodin, and Percocet contain acetaminophen [ 15 ]. Another study showed that online resources available to patients through health platforms and hepatology centers were lengthy and complex, highlighting the limited availability of easy-to-understand information for this patient population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the extensive available safety data, when used at appropriate dosage (up to 2-3g/day), acetaminophen should be the preferred first-line analgesic, antipyretic medication in patients with all forms of liver disease. However, research suggests limited awareness among clinicians and patients regarding acetaminophen's role in liver disease [26,27]. In a study encompassing over 2,000 healthcare providers, 40% of the participants were reluctant to endorse acetaminophen usage in patients with compensated cirrhosis.…”
Section: Acetaminophen "A Thriller In Liver Disease"mentioning
confidence: 99%
“…NSAIDs are particularly discouraged in patients with liver disease, especially in cases of cirrhosis, due to their heightened potential for causing kidney problems, gastrointestinal issues, and impairing platelet function [26][27][28][29]. NSAID-induced idiosyncratic hepatotoxicity has been extensively documented as well [27].…”
Section: Acetaminophen "A Thriller In Liver Disease"mentioning
confidence: 99%